Congenital diaphragmatic hernia: experience of 14 years - Rocha, G. (2013)
Aim. Over the last two decades, new therapies have emerged for the management of congenital diaphragmatic hernia (CDH). The aim of this paper was to review our experience in the management of newborns diagnosed with CDH over a 14-year period. Methods. Review of maternal and infant medical records, 1997-2010. Results. Eighty newborns with CDH; 21 (26%) were preterm and 28 (35%) of low birthweight (<2500 g), including 3 (4%) of very low birthweight (< 1500 g). Prenatal diagnosis was made in 53 (66%) cases. The location of the hernia was: left side 48 (90.5%); right 4 (7.5%); bilateral 1 (1%). Corrective surgery was performed in 58 (73%) patients. High frequency oscillatory ventilation was used in 10 (12.5%), inhaled nitric oxide in 18 (22.5%), sildenafil in 15 (18.7%) and extracorporeal membrane oxygenation in 1 (1%). The overall survival was 49% (N.=39). Since 2003, the overall survival raised to 64%. The survival rate of the appropriate for gestational age term newborns without other congenital/chromosomal anomaly or hydrops fetalis was 67% (24/36). Conclusion. Our survival rate for congenital diaphragmatic hernia has improved over the last 14 years, associated to the use of new therapies, such as high-frequency oscillation ventilation (HFOV), inhaled nitric oxide and sildenafil.